Reinventing the Amphiareion at Oropos - Wilding, Alexandra, (Mnemosyne, Supplements ;, 2022)
This book asks why politically-powerful entities invested in the Amphiareion, a sanctuary renowned for its precarity and dependency. The answer lies in unravelling the intricacies of the shrine's epigraphical record and the stories about the communities and individuals responsible for creating it. By explaining patterns in inscribed display against the backdrop of broader events and phenomena emerging within central Greece, this book revisits the Amphiareion's narrative and emphasises its political implications for its neighbours. This interpretation offers new perspectives on the sanctuary and exposes agents' manipulation of it in the course of reinventing their self-image in a changing Greek world.